A PHILOSOPHER OF SCIENCE LOOKS AT IDEALIZATION IN POLITICAL THEORY. Issue 1 (7th December 2016) - Ismael, Jenann
Abstract: Rawls ignited a debate in political theory when he introduced a division between the ideal and nonideal parts of a theory of justice. In the ideal part of the theory, one presents a positive conception of justice in a setting that assumes perfect compliance with the rules of justice. In the nonideal part, one addresses the question of what happens under departures from compliance. Critics of Rawls have attacked his focus on ideal theory as a form of utopianism, and have argued that political theory should be focused instead on providing solutions to the manifest injustices of the real world. In this essay, I offer a defense of the ideal/nonideal theory distinction according to which it amounts to nothing more than a division of labor, and explore some scientific analogies. Rawls's own focus on the ideal part of the theory, I argue, stems from a felt need to clarify the foundations of justice, rather than a utopian neglect of real world problems.